No Interactions of Stacked Bt Maize with the Non-target Aphid Rhopalosiphum padi and the Spider Mite Tetranychus urticae - Shu, Yinghua; Romeis, Jörg; Meissle, Michael (Frontiers in Plant Science, 2018)
In the agroecosystem, genetically engineered plants producing insecticidal Cry proteins from Bacillus thuringiensis (Bt) interact with non-target herbivores and other elements of the food web. Stacked Bt crops expose herbivores to multiple Cry proteins simultaneously. In this study, the direct interactions between SmartStax® Bt maize producing six different Cry proteins and two herbivores with different feeding modes were investigated. Feeding on leaves of Bt maize had no effects on development time, fecundity, or longevity of the aphid Rhopalosiphum padi (Hemiptera: Aphididae), and no effects on the egg hatching time, development time, sex ratio, fecundity, and survival of the spider mite Tetranychus urticae (Acari: Tetranychidae). The results thus confirm the lack of effects on those species reported previously for some of the individual Cry proteins. In the Bt maize leaves, herbivore infestation did not result in a consistent change of Cry protein concentrations. However, occasional statistical differences between infested and non-infested leaves were observed for some Cry proteins and experimental repetitions. Overall, the study provides evidence that the Cry proteins in stacked Bt maize do not interact with two common non-target herbivores.